Assessment of Public and Private Schools Physical Environment Standardized Features in Babylon Governorate: Comparative Study - Naji Yasser Saadoon (مجلة الموصل للتمريض, 2017)
Background and aim: creating a healthy school environment requires the involvement and participation of practically everyone in the school-students, administrators, teachers, school counselors, school nurses, nutrition services workers. The study aims to assess public and private schools physical environment standardized features in Babylon Governorate and to compare between public and private schools physical environment such features. Materials and method: A descriptive study, using the assessment approach, is carried out from July 2016 to April 2017. Probability, simple random sample, of (44) school principal, science teacher, and physical sport teacher is selected from (34) primary schools in Babylon Governorate. A questionnaire, of (44) items, is constructed for the purpose of the present study. Data are collected through the use of the constructed questionnaire and the application of the structured interview technique as means of data collection. Data are analyzed through the application of the descriptive statistical data analysis approach of frequencies, percentage, mean, and standard deviation and the inferential statistical data analysis approach of t-test. Results: The present study depicts that primary schools in Babylon Governorate experience deficiencies with respect to domains of the school environment standardized features, but private school have low deficiencies of such domains than public schools. Conclusions: The study concludes that both public and private schools had major deficiencies identified in their environment standardized features. However, public schools have a much higher proportions of deficiencies and are in most urgent need of actions. Private schools are also in need of remediation of deficiencies. Recommendations: The study recommends that further study with a large randomly selected sample of schools can be conducted to confirm the findings of this study and allow for greater generalizability. Advancement, in the measurement of standardized deficiencies, can take a place to advance the present study to the next level of rigor by eliminating redundant items and improving the reliability and validity of the questionnaire. Furthermore, evaluation of the improvement in deficiencies overtime using a longitudinal study design. Keyword: Assessment, School Physical Environment, Standardized Features, Private School, Public School.